INOVASI STRATEGI GURU DALAM MENGEMBANGKAN MEDIA PEMBELAJARAN PADA MASA PANDEMI DI MADRASAH ALIYAH NEGERI 4 BANYUWANGI - Kholifatuz Zulfa Nur Azizah; Yolla Rizky Presbianti (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UNSIQ Jawa Tengah, 2021)
Corona Virus Disease (COVID-19) has caused major changes in the habits of the Indonesian people, one of which is learning activities at the Madrasah Aliyah level. Learning that is usually carried out face-to-face can now only go through a virtual path or commonly called online. This incident attracted the author's attention to conduct a study using a phenomenological approach, especially with regard to strategies and findings, especially regarding Madrasah Aliyah Negeri 4 Banyuwangi which was carried out during the COVID-19 Pandemic. This study uses a causal-comparative quantitative approach. For technique data collection using the method of questionnaires, interviews and documentation. Meanwhile, for data analysis using t-test statistical analysis. This study draws several conclusions, namely: that online learning is supported by WhatsApp media and offline learning is carried out in schools face-to-face with a strategy of dividing class sessions.